2007
DOI: 10.1007/s11274-007-9604-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of lactic acid bacteria and yeasts in Airag and Tarag, traditional fermented milk products of Mongolia

Abstract: We used culture-and molecular-biology-based methods to investigate microbial diversity in the traditional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
127
5
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 27 publications
(26 reference statements)
13
127
5
1
Order By: Relevance
“…mesenteroides (28.5%) and Lactobacillus helveticus (19.2%) were the predominant LAB in kurut samples. The results are similar to the results reported by Watanabe et al in which Lactobacillus helveticus was the major LAB in traditional fermented Airag and Tarag in Mongolia (Watanabe et al, 2008). The current result for kurut is different from those in a previous report described by Sun et al 2010, which found that Lactobacillus delbrueckii subsp.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…mesenteroides (28.5%) and Lactobacillus helveticus (19.2%) were the predominant LAB in kurut samples. The results are similar to the results reported by Watanabe et al in which Lactobacillus helveticus was the major LAB in traditional fermented Airag and Tarag in Mongolia (Watanabe et al, 2008). The current result for kurut is different from those in a previous report described by Sun et al 2010, which found that Lactobacillus delbrueckii subsp.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, LAB count in most samples was larger than 7.9 lg CFU ml 1 . The results were similar to the fi ndings of previous studies on naturally fermented milks from parts of various countries, as shown from Watanabe et al, 2008 reported that total concentration of LAB in Airag and Tarag in traditional fermented milk products of Mongolia were 7.78 and 8.35 lg CFU ml 1 , respectively (Watanabe et al, 2008). In 2010, Sun et al found that LAB count of kurut in Qinghai in China ranged from 7.49 to 10.29 lg CFU ml 1 , with an average count of 8.69 0.88 lg CFU ml 1 .…”
Section: Enumeration and Isolation Of Labsupporting
confidence: 91%
See 1 more Smart Citation
“…Chromosomal DNA was used for an amplified fragment length polymorphism (AFLP) analysis and the sequence amplification of the 16S rRNA and recA genes from the novel isolates was conducted according to the method of Watanabe et al (2008). For discrimination of the strains, the AFLP analysis method was performed as described previously (Thompson et al, 2001), with the following modifications.…”
mentioning
confidence: 99%
“…It is produced from a mixed lactic acid and alcoholic fermentation of milk by lactic acid bacteria (LAB) and yeasts [1]. Moreover, koumiss was developed and known as a characteristic fermented product as well as for its unique physiological actions [2].…”
Section: Introductionmentioning
confidence: 99%